Randomized, double-blind trial of F14512, a polyamine-vectorized anticancer drug, compared with etoposide phosphate, in dogs with naturally occurring lymphoma - Boyé, Pierre (Oncotarget, 2020)
Purpose: F14512 is an epipodophyllotoxin derivative from etoposide, combined with a spermine moiety introduced as a cell delivery vector. The objective of this study was to compare the safety and antitumor activity of F14512 and etoposide phosphate in dogs with spontaneous non-Hodgkin lymphoma (NHL) and to investigate the potential benefit of F14512 in P-glycoprotein (Pgp) overexpressing lymphomas. Experimental Design: Forty-eight client-owned dogs with intermediate to high-grade NHL were enrolled into a randomized, double-blind trial of F14512 versus etoposide phosphate. Endpoints included safety and therapeutic efficacy. Results: Twenty-five dogs were randomized to receive F14512 and 23 dogs to receive etoposide phosphate. All adverse events (AEs) were reversible, and no treatment-related death was reported. Hematologic AEs were more severe with F14512 and gastrointestinal AEs were more frequent with etoposide phosphate. F14512 exhibited similar response rate and progression-free survival (PFS) as etoposide phosphate in the global treated population. Subgroup analysis of dogs with Pgp-overexpressing NHL showed a significant improvement in PFS in dogs treated with F14512 compared with etoposide phosphate. Conclusion: F14512 showed strong therapeutic efficacy against spontaneous NHL and exhibited a clinical benefice in Pgp-overexpressing lymphoma superior to etoposide phosphate. The results clearly justify the evaluation of F14512 in human clinical trials.